Does prior administration of the RBANS influence performance on subsequent neuropsychological testing?. Issue 4 (4th July 2018) - Calamia, Matthew; Roye, Scott; Lemke, Austin
ABSTRACT: The objective of this study was to determine whether administration of the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) prior to other neuropsychological testing improves performance on subsequent measures due to practice effects. Participants completed the RBANS and related neuropsychological measures of the same cognitive domain in one of two counterbalanced orders. A MANOVA and follow-up independent t-tests were used to examine whether or not completing one set of measures prior to the other was associated with score differences. Prior administration of the RBANS did not impact performance on subsequent testing. However, a significant effect of test order administration was found such that the group administered the RBANS second performed worse on RBANS delayed memory measures. This finding was likely due to proactive interference, given that items from initially administered memory measures presented as intrusions on subsequently administered memory measures. Current results indicate that the practice of administering the RBANS as a screener prior to administration of additional tests will not impact performance on the subsequent tests. Although practice effects were not found, clinicians and researchers administering memory measures with similar designs (e.g., verbal list-learning tasks) within a single testing session should be aware of the potential of interference effects.